Estimation of risk of damages of the main oil pipeline - Shil’ko Сергей Викторович; Kuz’minskiy Юрий Гарриевич (Chrezvychaynye situatsii: obrazovanie i nauka, 2008)
In order to predict emergencies in the conditions of oil pipeline transportation the risk factors of main oil pipeline damages are analyzed and an adaptive control system «monitoring means – computer model of transient processes – dispatcher – executive devices» is developed. Estimates of parameters of hydraulic calculations of oil pipeline transportation modes obtained from the data of RUE «Gomeltraisneft Druzhba» are given. The modeling results are used for forecasting stationary and transient modes, as well as for training of station operating personnel.